IEEE PES T&D 2010 2010
DOI: 10.1109/tdc.2010.5484412
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and test validation of a 15kV 24MVA Superconducting Fault Current Limiter

Abstract: High-power short-circuit test results and numerical simulations of a 15kV-24MVA distribution-class High Temperature Superconductor (HTS) Fault Current Limiters (FCL) are presented and compared in this paper. The FCL design was based on the nonlinear inductance model here described, and the device was tested at 13.1kV line-to-line voltage for prospective fault currents up to 23kArms, prior to its installation in the electric grid. Comparison between numerical simulations and fault test measurements show good ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 4 publications
(1 reference statement)
0
19
0
Order By: Relevance
“…The significant decrease in fault current is the outcome of this operation. According to the performed studies in Muljadi et al and Moriconi et al, Equation can be used to calculate the effective inductance of SISFCL, LEFF=NacAcoreB()iitalicaciac …”
Section: Operation Principles Of Sisfcl and Bsfclmentioning
confidence: 99%
“…The significant decrease in fault current is the outcome of this operation. According to the performed studies in Muljadi et al and Moriconi et al, Equation can be used to calculate the effective inductance of SISFCL, LEFF=NacAcoreB()iitalicaciac …”
Section: Operation Principles Of Sisfcl and Bsfclmentioning
confidence: 99%
“…Solving (1) and (3) simultaneously results in: (6) Note that all of the elements in (5) and (6) are either measured flux linkage values or an applied mmf. Hence, i and o can be completely determined from Tests 1 and 2.…”
Section: B Testmentioning
confidence: 99%
“…Hence, there is growing need for an accurate analytical model of the FCL, which can be easily incorporated into transient network simulation packages. The development of an accurate analytical model has already received some attention [6], [7]; however, the models developed to date do not include the AC to DC coupling effects of the device. It has been found that a "transformer" coupling effect exists between the AC and DC windings during a fault [5], which can have a significant impact on the performance of the FCL.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of the power loads demand and the expanding and integration of more renewable energy generation will consequently have an impact on the level of fault currents [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several solutions and techniques for limiting fault currents have been proposed in the past such as upgrading fast circuit breakers, system reconfiguration, installing transformers with higher impedance, current limiting fuses, air-core reactors, etc. [1]- [3]. However, those methods were practically limited due to high estimated costs, lack of system security and reliability.…”
Section: Introductionmentioning
confidence: 99%